5-Hydroxypyrimidine deoxynucleoside triphosphates are more efficiently incorporated into DNA by exonuclease-free Klenow fragment than 8-oxopurine deoxynucleoside triphosphates. - Purmal, A A (1994)
Recent studies with 8-oxodeoxyguanosine triphosphate (8-oxodGTP) have suggested that incorporation of oxidized nucleotides from the precursor pool into DNA may have deleterious effects. Here we show that 5-hydroxydeoxycytosine triphosphate (5-OHdCTP) and 5-hydroxydeoxyuridine triphosphate (5-OHdUTP) are more efficient substrates than 8-oxodGTP for Escherichia coli DNA polymerase I Klenow fragment lacking proofreading activity, while 8-oxodeoxyadenosine triphosphate (8-oxodGTP, 5-OHdCTP can mispair with dA in DNA but with lower efficiency. Since the 5-hydroxypyrimidines are present in normal and oxidized cellular DNA in amounts similar to the 8-oxopurines, these data suggest that enzymatic mechanisms might exist for removing them from the DNA precursor pools.